Distribution of organic agriculture in Brazil: a comparative analysis across geographic macro-regions - Andrade, Guilherme Alves de Souza; Santos, Ananias Francisco dos; Silva, Caroline Maria da; Espejo, Márcia Maria dos Santos Bortolocci (Science & Technology Journals, 2026)
The research aimed to map the distribution of organic agricultural production across Brazilian geographic macro-regions. Thus, this is a mixed-method, including descriptive, documentary and applied study, using data from the National Register of Organic Procedures of the Ministry ofAgriculture and Livestock (MAPA) from March 2023. Results indicate that primary vegetable production is the predominant organic activity among regions in Brazil, with the exception of the North region, which excels in organic extractive production. Although some crops, such as potatoes, cabbage and lettuce, are  common in several regions, each area also offers a specific heterogeneity of  products. This emphasizes the diversity of organic agriculture in Brazil and the importance of considering regional particularities when developing policies and strategies to support the sector throughout the country.
Keywords: agricultural sustainability; agricultural variety; environment; organic production